Green turtle and fish identification based on acoustic target strength - Sunardi Sunardi; Azrul Mahfurdz; Shoffan Saifullah (Universitas Ahmad Dahlan, 2018)
Fisherman accidentally caught sea turtles in their fishnet. It could be dangerous for its population. This study measures the turtle target strength (TS) using modified echosounder. The result could be used to improve the efficiency of turtle repellent device. The experiment conducted in a hatchery fiber tank contained saline water. The Green were 1, 3, 12 and 18 years old. This study used three species of fish, which serves to distinguish the value between fish and sea turtles. TS of the animals were calculated incorporating reference targets (sphere). The echo power of the turtle was compared with the solid steel sphere which is confirmed good agreements with the theoretical values. The echo power reference by applying Fast Fourier Transform (FFT) analysis has been used in calculating TS of the animal. The time domain of the echo evaluation in different angles shows the difference in the structure of the echo signal between the tortoise's body parts. This study reveals that high echo strength is acquired from the carapace and the plastron parts. The finding also showed that there are significant differences between 3, 12, 18 years old turtles and fish in every angle measurement.